2022
DOI: 10.1186/s12917-022-03457-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential of selected plant extracts to control severe subacute ruminal acidosis in vitro as compared with monensin

Abstract: Background In recent years, researchers have become increasingly interested in developing natural feed additives that can stabilize ruminal pH and thus prevent or eliminate the risk of severe subacute rumen acidosis. Herein, 3 experiments were conducted using a semi-automated in vitro gas production technique. In the experiment (Exp.) 1, the efficacy of 9 plant extracts (1.5 mg/ml), compared to monensin (MON; 12 μg/ml), to counteract ruminal acidosis stimulated by adding glucose (0.1 g/ml) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…This result agrees with Ahmed et al [117], who reported that both species of Lantana (L. camara and L. montevidensis) contained Flavonoid glycosides. In some cases, the antibacterial activities of flavonoid glycosides were equal to or higher than those of ciprofloxacin used as a reference antibiotic, suggesting that they might be effective antibiotics against these pathogenic bacteria [118].…”
Section: Phytochemical Analysissupporting
confidence: 93%
“…This result agrees with Ahmed et al [117], who reported that both species of Lantana (L. camara and L. montevidensis) contained Flavonoid glycosides. In some cases, the antibacterial activities of flavonoid glycosides were equal to or higher than those of ciprofloxacin used as a reference antibiotic, suggesting that they might be effective antibiotics against these pathogenic bacteria [118].…”
Section: Phytochemical Analysissupporting
confidence: 93%
“…Plants and their extracts contain large amounts of phytochemicals such as saponins, alkaloids, phenolic compounds (e.g., tannins and flavonoids), terpenoids and essential oils with antioxidant and antibacterial effects, which play an active role in stabilizing rumen pH and preventing SARA [ 27 ]. Extracts of cinnamon ( Cinnamonum cassia ), grape seed ( Vitis vinifera ), orange peel ( Citrus sinensis ), pomegranate peel ( Punica granatum ), propolis and guava ( Psidium guajava ) significantly increased the pH of mixed rumen microorganisms in in vitro fermentation, cinnamon extract also reduced lactate and total VFA concentrations in rumen fluid and improved the ratio of acetate to propionate, and could be used as an alternative to monensin to effectively control rumen acidosis [ 2 ]. The addition of a mixture of mangosteen peel ( Garcinia mangostana L.), rambutan peel ( Nephelium lappaceum L.), banana flower powder ( Musa sapientum L.) and cassava starch ( Manihot esculenta , rich in condensed tannins and saponins) to the diet had a good buffering effect on the decrease in rumen fluid pH caused by high concentrate rations, and the rumen pH increased from 5.74 to 6.19 after 8 h of feeding, and nutrient digestibility and efficiency of microbial nitrogen supply were significantly improved, while ruminal methane production and protozoa were significantly reduced [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants and their extracts contain large amounts of phytochemicals such as saponins, alkaloids, phenolic compounds (e.g., tannins and flavonoids), terpenoids and essential oils with antioxidant and antibacterial effects, which play an active role in stabilizing rumen pH and preventing SARA [27]. Extracts of cinnamon (Cinnamonum cassia), grape seed (Vitis vinifera), orange peel (Citrus sinensis), pomegranate peel (Punica granatum), propolis and guava (Psidium guajava) significantly increased the pH of mixed rumen microorganisms in in vitro fermentation, cinnamon extract also reduced lactate and total VFA concentrations in rumen fluid and improved the ratio of acetate to propionate, and could be used as an alternative to monensin to effectively control rumen acidosis [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feeding system represents a high risk for the presence of ruminal subacute acidosis episodes, which can negatively affect feed efficiency at this stage [ 2 ]. Improved ruminal fermentation by modulating certain microorganisms that reduce production of specific intermediate organic acids (i.e., lactate), as well as promoting an increase in ruminal propionate by reducing ruminal acetate and enhancing epithelial health and increasing nutrient absorption, is one of the ways to obtain better performance in ruminants that are fed high-energy diets [ 3 ]. A widely used tool to prevent this type of disorder and increase efficiency in the final stage of fattening is the antibiotic monensin (MON), which has been used for many years as a growth promoter in feedlots in several countries (i.e., Mexico, Canada, USA, Brazil, New Zealand, Argentina, Chile, and South Africa, among others) where its use is approved [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%